(6,3) Is the answer________________
Y= mx+b
Y= 1x -2
Good luck
Answer:
Step-by-step explanation:
Let the quadratic function be
We substitute into the equation to obtain;
We substitute to obtain;
We finally substitute to obtain;
We put equation (2) into equation (1) to get;
We add equation (4) and (5) to get;
We put into equation (5) to get;
The reqiured quadratic function is
Sequence 1,5,9,13,...
A(0) = 1 +4x0=1
A(1) =1 + 4x1 = 5
A(2) = 1+ 4x2= 9
A(3) = 1 +4x3=13
A(n)= 1+4n A(n-1) = 1+4(n-1) =1+4n-4= - 3+4n
A(n) - A(n-1) = (1+4n) - (-3=4n) = 4
A(n) = A(n-1) +4; 29 is the answer